Dinâmica da rizogênese de miniestacas e microestacas de Tectona grandis L.f. - Nunes, Camila Amorim (2021)
The objective of this study was to evaluate the dynamics of the rhizogenesis of teak mini-cuttings and micro-cuttings, by monitoring the emission of roots and their development. Mini-cuttings and micro-cuttings of two teak clones collected in clonal minijardim were used. For the application of exogenous auxin, the bases of the minicuttings and micro-cuttings were inserted in a powder containing exogenous auxin in four dosages (0, 500, 1000 and 1500 mg L-1). After auxin application, the mini-cuttings and micro-cuttings were rooted in a greenhouse. The variables evaluated were: percentages of survival, rhizogenesis, mini-cuttings and micro-cuttings with presence of callogenesis, average number of roots (≥ 2 mm in length), the average length of the largest root, dry mass of roots and aerial part. In the first chapter, the objective was to evaluate the rhizogenesis of Tectona grandis L.f. mini-cuttings submitted to different doses of exogenous auxins IBA and NAA, through the emission and development of roots, where the percentage of survival of mini-cuttings that ranged from 95.8% to 100%. For the variable percentage of mini-cuttings with the presence of callogenesis the highest value was 41.67%, found at 21 days, for the dosage 1000 mg L-1 regardless of the auxin used. The doses of 1000 mg L-1 of NAA and 500 mg L-1 of IBA presented the highest results for average number of roots, average length of the largest root (cm) and percentage of rhizogenesis. There is a reduction in expenditure when using the auxin NAA compared to IBA. In the second chapter the objective was to evaluate the rhizogenesis of Tectona grandis L.f. mini-cuttings and micro-cuttings submitted to different doses of exogenous auxin AIB, through the emission and development of roots. The percentage of survival of the mini-cuttings and micro-cuttings varied from 83.75% to 97.5%, when they left the greenhouse at 40 days. Except for the variable survival percentage no influence was observed on the type of cuttings used, minicuttings and micro-cuttings. The use of AIB in the dosages tested did not show significant effects for any of the variables analyzed.